Perancangan Sistem Informasi Peminjaman dan Pengembalian BRM Rawat Jalan di Rumah Sakit Husada Utama - Lidya Nur Fatimatuz Zuhro; Ida Nurmawati; Rossalina Adi Wijayanti; Gilang Nur Permana (Politeknik Negeri Jember, 2020)
Borrow and return outpatient medical records at the Husada Utama Hospital in Surabaya still uses manuals by referring to the date of discharge from the hospital to search for files that have not been returned or for file tracking so that it can cause difficulties for officers in tracking outpatient medical records. Data of delay in the return of outpatient medical records in February-March 2020 counted for 117 (14.88%) of the total files late from the 786 total outgoing files. SOP (Standard Operational Procedure) that applies at Husada Utama Hospital regarding hospital service standards is explained by the medical records of Specialist Practices which are returned within 1X24 hours on the same day. While the medical record file in the inpatient room is submitted no later than 2X24 hours after the date the patient is discharged from the hospital. This researchÂ was aimed to design a web-based outpatient medical records and loan information system at the Husada Utama Hospital in Surabaya. The type of research is qualitative research with data collection methods of observation and interviews. The subjects of this research were the head of the medical record and the outpatient medical record officer. The method used by researchers is the waterfall method. The results of this research can be seen that the design of information systems for borrowing and returning outpatient medical record files are made according to the needs of users, making the system starts from the needs analysis so it produce a system design that suits your needs.